ATTAINING THE DEMOGRAPHIC BONUS IN INDONESIA - Warsito, Teguh (Politeknik Keuangan Negara STAN, 2019)
Indonesia is experiencing the demographic bonus when the proportion of a working-age population is higher than a non-working-age population. This bonus will achieve its peak in 2030, then the proportion will decrease gradually. After that, Indonesia will face the demographic burden. Demographic bonus is very important to be utilized since it gives an opportunity to boost economic growth. However, after this bonus happens, the problems will Â arise in the demographic burden period. This paper will analyze demographic phenomena and offer several policies that can be taken by the government to attain the bonus and to lessen the bad impact of the burden using literature review analysis. According to the results of this paper, the government should focus on decreasing an unemployment rate, providing social infrastructure, and educating people.